Contiguous cutaneous inflammation secondary to an aspergillus sinusitis - Lefranc, H; Brugière, C; Plisson, L; Comoz, F; Verneuil, L; Dompmartin, A (Annales de dermatologie et de vénéréologie, 2018)
Contiguous skin inflammation is a poorly described entity. It constitutes a cutaneous manifestation of an underlying ongoing process (infectious, inflammatory or neoplastic). Sinusitis is a known cause. We report the case of a 70-year-old patient consulting for an ongoing centrofacial inflammatory plaque. Cutaneous biopsy revealed a polymorphic inflammatory infiltrate, and cutaneous microbiological specimens were negative. A facial CT-scan showed left maxillary sinusitis. Intra-sinus samples obtained at surgery showed aspergillus. Voriconazole combined with maxillary sinus surgery resulted in healing of the facial plaque. There have been only two published cases of contiguous skin inflammation related to sinusitis but no reported cases caused by aspergillus sinusitis. Herein we report the third case of contiguous skin inflammation associated with sinusitis, which is also the first related to aspergillus sinusitis.